Technical Feasibility and Physiological Relevance of Hypoxic Cell Culture Models - Pavlacky, Jiri; Polak, Jan (Frontiers in Endocrinology, 2020)
Hypoxia is characterized as insufficient oxygen delivery to tissues and cells in the body and is prevalent in many human physiology processes and diseases. Thus, it is an attractive state to experimentally study to understand its inner mechanisms as well as to develop and test therapies against pathological conditions related to hypoxia. Animal models in vivo fail to recapitulate some of the key hallmarks of human physiology, which leads to human cell cultures; however, they are prone to bias, namely when pericellular oxygen concentration (partial pressure) does not respect oxygen dynamics in vivo. A search of the current literature on the topic revealed this was the case for many original studies pertaining to experimental models of hypoxia in vitro. Therefore, in this review, we present evidence mandating for the close control of oxygen levels in cell culture models of hypoxia. First, we discuss the basic physical laws required for understanding the oxygen dynamics in vitro, most notably the limited diffusion through a liquid medium that hampers the oxygenation of cells in conventional cultures. We then summarize up-to-date knowledge of techniques that help standardize the culture environment in a replicable fashion by increasing oxygen delivery to the cells and measuring pericellular levels. We also discuss how these tools may be applied to model both constant and intermittent hypoxia in a physiologically relevant manner, considering known values of partial pressure of tissue normoxia and hypoxia in vivo, compared to conventional cultures incubated at rigid oxygen pressure. Attention is given to the potential influence of three-dimensional tissue cultures and hypercapnia management on these models. Finally, we discuss the implications of these concepts for cell cultures, which try to emulate tissue normoxia, and conclude that the maintenance of precise oxygen levels is important in any cell culture setting.